2021 Olympic Games Tokyo: Safety issues and protection against COVID-19 transmission - Ribas, R. M.; Campos, P. A.; Brito, C. S.; Dantas, R. C. (Journal of Global Infectious Diseases, 2020)
Tokyo will soon host one of the world's biggest sporting events, Olympic Games that are expected to happen on July 23, 2021. This event is a great opportunity and potential for triggering a new global dissemination of not only the coronavirus but also bacteria containing successful antimicrobial drug-resistant determinants.